(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
The focus of the present study is to make a comparison between CAI and traditional methods in learning concepts of Mathematics. The sample comprising of 120 school students of 10th class of two schools of Amritsar city. The analysis was found that the performance of the Xth class students taught through CAI has been better as compared to those taught through traditional methods. The students remain actively involved in the lesson and become willing participants in the demonstration